Antioxidant Activity from Various Tomato Processing - Retno Sri Iswari; R Susanti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2016)
Tomato is one of the high antioxidant potential vegetables. Nowadays, there are many techniques of tomato processings instead of fresh consumption, i.e. boiled, steamed, juiced and sauteed. Every treatment of cooking will influence the chemical compound inside the fruits and the body's nutrition intake. It is important to conduct the research on antioxidant compound especially lycopene, β-carotene, vitamin C, α-tocopherol, and its activity after processing. This research has been done using the experimental method. Tomatoes were cooked into six difference ways, and then it was extracted using the same procedure continued with antioxidant measurement. The research results showed that steaming had promoted the higher antioxidant numbers (lycopene. α-tocopherol, β-carotene and vitamin C) and higher TCA and antioxidant activities in the tomatoes than other processings. It was indicated that steaming was the best way to enhance amount, capacity and activities of antioxidants of the tomatoes.